EPEN-25. KANSL1 GAIN AND FUSION - A NOVEL ALTERATION IN CHILDHOOD EPENDYMOMA. Issue 2 (22nd June 2018) - Margolin-Miller, Yulia; Toledano, Helen; Sela-Tzuriano, Lital; Hameiri-Grossman, Michal; Michowiz, Shalom; Fichman-Horn, Suzanna; Feinmesser, Meora; Pfister, Stefan; Witt, Hendrik; Yaniv, Isaac; Avigad, Smadar
Abstract: Ependymoma is a malignant pediatric brain tumor, often incurable with current treatment regimens. We aimed to identify new genes involved in pediatric ependymoma using copy number SNP array analysis. We analyzed 34 primary tumors, in 10 cases we analyzed the paired diagnosis-relapse samples and in 5 of them we also analyzed the corresponding peripheral blood (PB) sample. The most prevalent alterations identified were gain of 8q (18%), deletion of 10q (18%), gain of 11q (12%) and gain of 17q (53%). The locus of the 17q21.31 gain contains only one gene - KANSL1 (KAT8 regulatory NSL complex subunit 1) gene. The gain affected exons 1–4 of the gene. This gain was identified in 9 out of the 10 (90%) relapse samples and in all of the PB samples. The gain was validated at the RNA level and a significant overexpression of KANSL1 mRNA was detected in the samples exhibiting gain versus the samples with normal copy number (p=0.04). KANSL1 is part of the NSL complex which functions as a histone acetyltransferase. The 17q21.31 locus contains a common inversion duplication polymorphism enriched in European populations. Recently, a new fusion was discovered in high frequencies in adult malignancies between KANSL1 and ARL17, termed KANSARL, both located on 17q21.31. KANSARL fusion was detected in 71% of our samples. All the samples that exhibited gain of KANSL1 were positive for the KANSARL fusion. Our results suggest that the gain precedes the formation of the fusion which may be a predisposing event in ependymoma.